Diversidade críptica em traíras Hoplias malabaricus (Bloch, 1794) da bacia atlântico nordeste ocidental - (:unkn) unknown (UNIVERSIDADE FEDERAL DO OESTE DO PARÁ, 2024)
Molecular analyses using DNA barcoding have been widely applied for species identification and biodiversity studies. In fish, the mitochondrial gene COI (Cytochrome c Oxidase subunit I) is the most commonly used marker for DNA barcoding. This study analyzed molecular variation through DNA barcoding in a population sample of trahiras (Hoplias malabaricus) collected from the Northeastern Atlantic Basin (BANOC). A total of 106 COI sequences were examined: 21 from fish collected at the following locations—Caeté River, Grande Stream, Itapecuru River, Periá River, Pericumã River, Mearim River, and Urumajó River—while 63 sequences were obtained from public databases and previous studies. Additionally, 20 samples from Suriname and two samples of Hoplias lacerdae were included for comparison as an outgroup. The sequences were submitted to the BOLD Systems platform, identifying two evolutionarily distinct lineages of H. malabaricus from BANOC, which were grouped into two BINs (Barcode Index Numbers). One group was widely distributed and associated with BIN, while the other was restricted to the Itapecuru River and Grande Stream sub-basins, corresponding to BIN. The genetic distance between the two groups was 2.9%, while the variation within AFU2064 was estimated at 2%. The study revealed haplotypic diversity (0.7582) and indicated the presence of multiple lineages within the H. malabaricus complex, highlighting the importance of conservation strategies that account for this diversity. BIN ACR9466 may represent a possible new species yet to be described.
Keywords: Biodiversidade; Diversidade genética; Hoplias malabaricus; CIÊNCIAS BIOLÓGICAS